Regional differences and convergence of green total factor productivity in pig breeding: evidence from China - Wang, Linwei; Chang, Qian; Kong, Rong (Frontiers in Environmental Science, 2023)
Achieving green, healthy, and circular development in China's pig industry does not enable the adjustment of rural industrial structure but also helps attain community demand for safe meat, thus playing a critical role in promoting sustainable agricultural development. This research utilizes panel data from 21 provinces (districts) in China from 2004 to 2021 to construct an evaluation system for green total factor productivity in pig breeding (PGTFP). The super-efficient slacks-based measure (SBM) model is employed to measure PGTFP. Conversely, the regional disparities in PGTFP are determined using the Dagum Gini coefficient method. Furthermore, we analyzed the convergence state of pig breeding in different regions. The findings indicate that PGTFP in China exhibited fluctuations, with the highest PGTFP observed in the constrained development areas. The development differences of PGTFP across the entire country have gradually diminished, with the greatest development differences observed within potential growth areas. Furthermore, disparities between the focused development areas and potential growth areas are most pronounced, primarily attributable to the super-variable density. Both α and β convergence are observed for PGTFP at the national level and within each breeding area. However, the α convergence pattern during COVID-19 is not obvious. Consequently, formulate differentiated farming development strategies, and foster the coordinated development of pig breeding in all regions have become imperative. Meanwhile, prepare contingency prevention measures to promote stable and high-quality development of pig breeding.